Training Stakeholders on Major Seasonal Forecast for The South of Ghana - Martey, Francisca; Yeboah, Stephen (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Ghana Meteorological Agency (GMet) has formed a partnership with the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) to deliver training programs on seasonal forecasting. These training sessions target farmers, media personnel, and agricultural extension officers in two regions of Ghana, namely Cape Coast in the Central Region and Kintampo in the Bono East region.